Life Survival Strategy of Street Children and Accompaniment - Ginting, Mishella Serafina Br; Shofwan, Imam (Edukasi, 2021)
Family poverty is a factor in the emergence of the phenomenon of street children, the inability to fulfill life expenses is the reason for them to survive in the streets by doing activities such as selling newspapers, busking, begging, market workers, street vendors, scavenging used goods, polishing shoes, cleaning vehicles services at traffic lights, collecting used goods, and so on. The purpose of this study was to find out how the live survival strategy for street children and to find out the efforts to assist street children by the Setara Foundation in Semarang City. The type of research used is descriptive qualitative research. The data sources in this study were four street children who lived on the streets for more than 2 years and a manager of the Semarang City Setara Foundation. Data collection techniques used are observation, interviews, and documentation. Validity checking technique using source triangulation. The research located at the Tugu Muda area of Semarang City and the Setara Foundation office. The results of this study are a form of the subject's survival strategy by applying active survival strategies by working on the streets from an early age independently, such as selling newspapers and tissues, passive survival strategies by saving food or eating with potluck dishes, and network survival strategies by maintaining relationships with other street children. The handling carried out by the Setara Foundation involves children that considered at risk of streets life and children that is already involving at streets in various activities, such as preventing children who are at risk of taking to the streets and becoming victims of CSEC, involving children in alternative education, developing children's forums, developing child protection networks, and legal assistance to street children, especially those who are exploited, children in conflict with the law, and sexual violence. The Setara Foundation has several mentoring programs for street children to avoid CSEC and legal assistance for children who are victims of violence and CSEC.